Unveiling the Role of the Microalga Nannochloropsis gaditana in the Biogenic Synthesis of Zinc Oxide - Tinello, Susanna; Mazzariol, Chiara; Pilotto, Carlo; Dolcet, Paolo; Perin, Giorgio; Battistolli, Matteo; Sandrelli, Federica; Morosinotto, Tomas; Gross, Silvia (Sustainability & Circularity NOW, 2025)
The increasing demand for environmentally friendly and sustainable approaches to materials synthesis calls, inter alia, for the development of biogenic methods to produce inorganic compounds by exploiting biological macromolecules and organisms. This study focuses on the optimization of a one-pot green synthesis of zinc oxide (ZnO) particles using microalgae extracts as a biogenic agent. Microalgae serve as an environmentally friendly platform for biotechnological applications due to their ability to promote the synthesis of valuable chemicals, thanks to their active components, such as enzymes. A systematic investigation of the experimental parameters revealed that both the reaction temperature and the concentration of microalgae extract significantly influenced the crystallite size of ZnO nanoparticles. In addition, the role of sodium hydroxide as a precipitating agent when used in combination with microalgae extract was addressed and compared with existing literature. The results indicate that microalgae extract can act as a scaffold to promote the controlled growth of ZnO particles. Antimicrobial tests also showed that ZnO particles synthesized with microalgae exhibited comparable antimicrobial activity with respect to ZnO produced by conventional methods. These results highlight the potential of microalgae as biogenic agents for the green synthesis of ZnO particles with tunable structural and antimicrobial properties.
Keywords: Green chemistry; Zinc oxide; Microalgae; Biogenic